Heart rate turbulence in Chagas disease. - Ribeiro ALP; Schmidt G; Sousa MR; Lombardi F; Gomes MED; Perez AA; Barros MVL; Machado FS; Rocha MOC (Pacing & Clinical Electrophysiology, 2003)
Heart rate turbulence (HRT) quantifies the biphasic response of the sinus node to ventricular premature complexes (VPCs) and is a powerful electrocardiogram related risk predictor. VPCs are frequent in Chagas disease, a potentially lethal illness, and can hamper the analysis by conventional methods of autonomic heart control. The aim of the study was to examine HRT in patients with Chagas disease. Chagas disease patients and healthy controls (group 0, n = 11) without other diseases were submitted to a standardized protocol, including electrocardiogram, echocardiography, and 24-hour Holter monitoring. Chagas disease patients were divided according to their left ventricular systolic function: normal (group 1, n = 103) and reduced ejection fraction (group 2, n = 23). Two HRT indices, turbulence onset (TO) and turbulence slope (TS), were calculated and compared among groups after adjustment for covariates like the prevalence of VPCs and the mean heart rate. Chagas disease patients had significantly altered TO (group 1: -0.0186, group 2: -0.0126) and TS (group 1: 10.844, group 2: 7.870) values in comparison with controls (TO -0.0256, TS 19.829); P < 0.001 for both comparisons. In conclusion, HRT data may be useful in the electrocardiographic analysis of autonomic heart control in Chagas disease. Its prognostic value remains to be determined.